Open Access

Almost increasing sequences and their new applications

Journal of Inequalities and Applications20132013:207

https://doi.org/10.1186/1029-242X-2013-207

Received: 9 January 2013

Accepted: 12 April 2013

Published: 25 April 2013

Abstract

In this paper, we generalize a known theorem dealing with | C , 1 | k summability factors to the | C , α | k summability factors of infinite series using an almost increasing sequence. This theorem also includes some known and new results.

MSC:26D15, 40D15, 40F05, 40G05.

Keywords

increasing sequences Cesàro mean summability factors Hölder inequality Minkowski inequality

1 Introduction

A positive sequence ( b n ) is said to be an almost increasing sequence if there exists a positive increasing sequence ( c n ) and two positive constants A and B such that A c n b n B c n (see [1]). Let a n be a given infinite series with the sequence of partial sums ( s n ) . By t n α we denote the n th Cesàro mean of order α, with α > 1 , of the sequence ( n a n ) , that is,
t n α = 1 A n α v = 0 n A n v α 1 v a v ,
(1)
where
A n α = ( n + α n ) = ( α + 1 ) ( α + 2 ) ( α + n ) n ! = O ( n α ) , A n α = 0 for  n > 0 .
(2)
The series a n is said to be summable | C , α | k , k 1 , if (see [2])
n = 1 1 n | t n α | k < .
(3)

If we take α = 1 , then | C , α | k summability reduces to | C , 1 | k summability.

2 Known result

Many works dealing with an application of almost increasing sequences to the absolute Cesàro summability factors of infinite series have been done (see [311]). Among them, in [10], the following main theorem dealing with | C , 1 | k summability factors has been proved.

Theorem A Let ( φ n ) be a positive sequence and ( X n ) be an almost increasing sequence. If the conditions
n = 1 n | Δ 2 λ n | X n < ,
(4)
| λ n | X n = O ( 1 ) as n ,
(5)
φ n = O ( 1 ) as n ,
(6)
n Δ φ n = O ( 1 ) as n ,
(7)
v = 1 n | t v | k v X v k 1 = O ( X n ) as n
(8)

are satisfied, then the series a n λ n φ n is summable | C , 1 | k , k 1 .

3 The main result

The aim of this paper is to generalize Theorem A to the | C , α | k summability in the following form.

Theorem Let ( φ n ) be a positive sequence and let ( X n ) be an almost increasing sequence.

If the conditions (4), (5), (6) and (7) are satisfied, and the sequence ( w n α ) defined by (see [12])
w n α = { | t n α | , α = 1 , max 1 v n | t v α | , 0 < α < 1 ,
(9)
satisfies the condition
v = 1 n ( w v α ) k v X v k 1 = O ( X n ) as n ,
(10)

then the series a n λ n φ n is summable | C , α | k , 0 < α 1 , ( α 1 ) k > 1 and k 1 .

Remark It should be noted that if we take α = 1 , then we get Theorem A. In this case, condition (10) reduces to condition (8) and the condition ‘ ( α 1 ) k > 1 ’ is trivial.

We need the following lemmas for the proof of our theorem.

Lemma 1 [13]

If 0 < α 1 and 1 v n , then
| p = 0 v A n p α 1 a p | max 1 m v | p = 0 m A m p α 1 a p | .
(11)

Lemma 2 [14]

Under the conditions (4) and (5), we have
n X n | Δ λ n | = O ( 1 ) as n ,
(12)
n = 1 X n | Δ λ n | < .
(13)

4 Proof of the Theorem

Let ( T n α ) be the n th ( C , α ) mean, with 0 < α 1 , of the sequence ( n a n λ n φ n ) .

Then, by (1), we find that
T n α = 1 A n α v = 1 n A n v α 1 v a v λ v φ n .
(14)
Thus, applying Abel’s transformation first and then using Lemma 1, we have that
T n α = 1 A n α v = 1 n 1 Δ ( λ v φ n ) p = 1 v A n p α 1 p a p + λ n φ n A n α v = 1 n A n v α 1 v a v = 1 A n α v = 1 n 1 ( λ v Δ φ v + φ v + 1 Δ λ v ) p = 1 v A n p α 1 p a p + λ n φ n A n α v = 1 n A n v α 1 v a v , | T n α | 1 A n α v = 1 n 1 | λ v Δ φ v | | p = 1 v A n p α 1 p a p | + 1 A n α v = 1 n 1 | φ v + 1 Δ λ v | | p = 1 v A n p α 1 p a p | + | λ n φ n | A n α | v = 1 v A n v α 1 v a v | 1 A n α v = 1 n 1 A v α w v α | λ v | | Δ φ v | + 1 A n α v = 1 n 1 A v α w v α | φ v + 1 | | Δ λ v | + | λ n | | φ n | w n α = T n , 1 α + T n , 2 α + T n , 3 α .
To complete the proof of the theorem, by Minkowski’s inequality, it is sufficient to show that
n = 1 n 1 | T n , r α | k < for  r = 1 , 2 , 3 .
Now, when k > 1 , applying Hölder’s inequality with indices k and k , where 1 k + 1 k = 1 , we get that
n = 2 m + 1 n 1 | T n , 1 α | k n = 2 m + 1 n 1 ( A n α ) k { v = 1 n 1 A v α w v α | Δ φ v | | λ v | } k = O ( 1 ) n = 2 m + 1 1 n 1 + α k v = 1 n 1 ( v α ) k ( w v α ) k | Δ φ v | k | λ v | k { v = 1 n 1 1 } k 1 = O ( 1 ) n = 2 m + 1 1 n 2 + ( α 1 ) k v = 1 n 1 v α k ( w v α ) k | λ v | k 1 v k = O ( 1 ) v = 1 m v α k ( w v α ) k v k | λ v | k n = v + 1 m + 1 1 n 2 + ( α 1 ) k = O ( 1 ) v = 1 m v α k ( w v α ) k v k | λ v | k v d x x 2 + ( α 1 ) k = O ( 1 ) v = 1 m ( w v α ) k | λ v | | λ v | k 1 1 v = O ( 1 ) v = 1 m ( w v α ) k | λ v | 1 v X v k 1 = O ( 1 ) v = 1 m 1 Δ | λ v | r = 1 v ( w r α ) k r X r k 1 + O ( 1 ) | λ m | v = 1 m ( w v α ) k v X v k 1 = O ( 1 ) v = 1 m | Δ λ v | X v + O ( 1 ) | λ m | X m = O ( 1 ) as  m
by virtue of the hypotheses of the theorem and Lemma 2. Again, we get that
n = 2 m + 1 n 1 | T n , 2 α | k n = 2 m + 1 n 1 ( A n α ) k { v = 1 n 1 A v α w v α | φ v + 1 | | Δ λ v | } k = O ( 1 ) n = 2 m + 1 1 n 1 + α k { v = 1 n v α ( w v α ) | Δ λ v | } k = O ( 1 ) n = 2 m + 1 1 n 1 + α k v = 1 n 1 v α k ( w v α ) k | Δ λ v | k { v = 1 n 1 1 } k 1 = O ( 1 ) n = 2 m + 1 1 n 2 + ( α 1 ) k v = 1 n 1 v α k ( w v α ) k | Δ λ v | k = O ( 1 ) v = 1 m v α k ( w v α ) k | Δ λ v | | Δ λ v | k 1 n = v + 1 m + 1 1 n 2 + ( α 1 ) k = O ( 1 ) v = 1 m v α k ( w v α ) k | Δ λ v | v k 1 X v k 1 v d x x 2 + ( α 1 ) k = O ( 1 ) v = 1 m v | Δ λ v | ( w v α ) k v X v k 1 = O ( 1 ) v = 1 m Δ ( v | Δ λ v | ) r = 1 v ( w r α ) k r X r k 1 + O ( 1 ) m | Δ λ m | v = 1 m ( w v α ) k v X v k 1 = O ( 1 ) v = 1 m 1 v | Δ 2 λ v | X v + O ( 1 ) v = 1 m 1 X v | Δ λ v | + O ( 1 ) m | Δ λ m | X m = O ( 1 ) as  m
by hypotheses of the theorem and Lemma 2. Finally, as in T n , 1 α , we have that
n = 1 m n 1 | T n , 3 α | k = n = 1 m n 1 | λ n φ n w n α | k = O ( 1 ) n = 1 m ( w n α ) k | λ n | n X n k 1 = O ( 1 ) as  m

by virtue of the hypotheses of the theorem and Lemma 2. This completes the proof of the theorem. Also, if we take k = 1 , then we get a new result concerning the | C , α | summability factors of infinite series.

Declarations

Acknowledgements

Dedicated to Professor Hari M Srivastava.

The author expresses his thanks to the referees for their useful comments and suggestions.

Authors’ Affiliations

(1)
Bahçelievler

References

  1. Bari NK, Stečkin SB: Best approximation and differential properties of two conjugate functions. Tr. Mosk. Mat. Obŝ. 1956, 5: 483–522. (in Russian)Google Scholar
  2. Flett TM: On an extension of absolute summability and some theorems of Littlewood and Paley. Proc. Lond. Math. Soc. 1957, 7: 113–141.MathSciNetView ArticleMATHGoogle Scholar
  3. Bor H: An application of almost increasing sequences. Math. Inequal. Appl. 2002, 5(1):79–83.MathSciNetMATHGoogle Scholar
  4. Bor H, Srivastava HM: Almost increasing sequences and their applications. Int. J. Pure Appl. Math. 2002, 3: 29–35.MathSciNetMATHGoogle Scholar
  5. Bor H: A study on almost increasing sequences. JIPAM. J. Inequal. Pure Appl. Math. 2003., 4(5): Article ID 97Google Scholar
  6. Bor H, Leindler L: A note on δ -quasi-monotone and almost increasing sequences. Math. Inequal. Appl. 2005, 8(1):129–134.MathSciNetMATHGoogle Scholar
  7. Bor H, Özarslan HS: On the quasi-monotone and almost increasing sequences. J. Math. Inequal. 2007, 1(4):529–534.MathSciNetView ArticleMATHGoogle Scholar
  8. Bor H: An application of almost increasing sequences. Appl. Math. Lett. 2011, 24(3):298–301. 10.1016/j.aml.2010.10.009MathSciNetView ArticleMATHGoogle Scholar
  9. Bor H: On a new application of almost increasing sequences. Math. Comput. Model. 2011, 53(1–2):230–233. 10.1016/j.mcm.2010.08.011MathSciNetView ArticleMATHGoogle Scholar
  10. Sulaiman WT: On a new application of almost increasing sequences. Bull. Math. Anal. Appl. 2012, 4(3):29–33.MathSciNetMATHGoogle Scholar
  11. Bor H, Srivastava HM, Sulaiman WT: A new application of certain generalized power increasing sequences. Filomat 2012, 26(4):871–879. 10.2298/FIL1204871BMathSciNetView ArticleMATHGoogle Scholar
  12. Pati T: The summability factors of infinite series. Duke Math. J. 1954, 21: 271–284. 10.1215/S0012-7094-54-02127-4MathSciNetView ArticleMATHGoogle Scholar
  13. Bosanquet LS: A mean value theorem. J. Lond. Math. Soc. 1941, 16: 146–148.MathSciNetView ArticleMATHGoogle Scholar
  14. Mazhar SM: Absolute summability factors of infinite series. Kyungpook Math. J. 1999, 39: 67–73.MathSciNetMATHGoogle Scholar

Copyright

© Bor; licensee Springer 2013

This article is published under license to BioMed Central Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.